Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial rural de Cumbaratza del Cantón Zamora. Período 2022 - Arévalo Morocho, Evelyn Yadira (2024)
This Curricular Integration Work entitled FINANCIAL AUDIT TO THE AUTONOMOUS DECENTRALIZED PARROQUIAL RURAL PARISH GOVERNMENT OF CUMBARATZA OF CANTON ZAMORA, PERIOD 2022. To fulfill the financial audit questionnaires were applied to collect general information, accounting, and legal documentation necessary to know the entity; then the internal control system was evaluated, it was determined the reasonableness of balances, the legality of their transactions, and procedures under audit programs; also the final audit report containing comments, conclusions, and recommendations were prepared. In the preparation of the financial audit, a preliminary planning report of the audited institution was made to collect information; the internal control evaluation of the components was made, to determine weaknesses and the balances presented in the financial statements, which were verified and checked, determining compliance with current regulations and generally accepted accounting principles. By executing the substantive and control procedures for the different components of the financial statements established in the audit programs, each working paper was analyzed, verified, and designed, based on the internal control standards. This process made it possible to determine the reasonableness of the balances presented in the financial statements, except for non-current assets, in which movable assets were identified that should be disposed of because they were in poor condition. The final audit report was issued where the findings are reflected, detailing conclusions and recommendations to check and verify each of the financial operations executed in the entity to determine deficiencies in the accounting process and that the authorities make efficient decisions according to the internal control standards.